(untitled) (Veterinary Science, 2019)
Previous studies have determined that hydro-alcoholic extracts of Equisetum giganteum (EE) and Cortaderia selloana (ECo) prevent gastric harm induced by stress in Mus musculus mice expose to hypothermia and immobilization. The aim of this study was to determine if the protective effect of indomethacin (ID), a non-steroid anti-inflammatory drug, on the gastric mucosa, is mediated by prostaglandin. The animals were assigned into one of the six groups of five animals each. The Blank Group (BG) received an oral dose (OD) of an excipient (Ex) composed of hydroxyl methyl cellulose and tweed 80; the Control Group (CG) received excipient plus 5 mg/kg subcutaneously of ID; the Equisetum Group (EG) with EE; the Equisetum Indomethacin Group (EIG) with EE and ID; the Cortaderia Group (CoG) with Eco and the Cortaderia Indomethacin Group (CoIG) with Co and ID. The doses utilized in the animals were obtained from 1 gram of dried aerial plant parts extracted with ethanol-water (1:1; v/v) and re-suspended with Ex until 0.5 ml. The ID groups (CG, EIG, CoIG) received the doses 1 hour before the beginning of the trial, and thereafter all the groups were subjected to stress during 4 hours at 22 °C. In order to assess the gastric harm, the percentage of ulcer inhibition was calculated as follow [(AUControl or Blank Groups – AUTreated Group/AUControl or Blank Group) x 100] where AU is the Ulcerated Area . The administration of ID induced a higher degree of gastric damage in the CG than in the BG (p≤0.01). The EE administration prevented the gastric damage in four mice of the EG, but the administration of ECo prevented the damage in all the animals of the CoG (p≤0.01), demonstrating no gastroprotective effect of EE when was given concomitantly with ID. The ECo showed significant gastroprotective effects when was administered simultaneously with ID (p≤0.01) suggesting that prostaglandin would have no effect in the protection of the gastric mucosa. The findings of vegetable drugs with the observed actions are of interest in order to both replace drugs with an antagonist of H2 and inhibitors of protons pump actions, because of its side effects when are prescribed during an extended period of time.